2019
DOI: 10.1088/2058-6272/ab341d
|View full text |Cite
|
Sign up to set email alerts
|

Development of the HL-2M digital pulse analysis system

Abstract: A digital pulse analysis system is an important diagnostic system in nuclear physics experimental research. In response to the demand for reflecting the particle state in a nuclear physics experiment, we have designed and developed a real-time digital pulse analysis system and applied it to the digital nuclear pulse waveform discrimination of different detectors in the HL-2M tokamak. The system is based on the peripheral component interconnect extensions for instrumentation (PXI) platform, while its software w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The results of the UV absorption spectra of the nano-silver colloid are shown in figure 3(a). The transparent bright yellow nano-silver colloid has a peak around 415 nm, which is a typical surface plasma resonance (SPR) peak for AgNPs in the region of 400-450 nm, and the result indicates that the nano-powder has successfully dispersed and the colloid has finally formed [30,31]. Moreover, from the TEM image is illustrated in figure 3(b), it can be observed that the particle diameter is about 80 nm.…”
Section: Nano-silver Colloidmentioning
confidence: 91%
“…The results of the UV absorption spectra of the nano-silver colloid are shown in figure 3(a). The transparent bright yellow nano-silver colloid has a peak around 415 nm, which is a typical surface plasma resonance (SPR) peak for AgNPs in the region of 400-450 nm, and the result indicates that the nano-powder has successfully dispersed and the colloid has finally formed [30,31]. Moreover, from the TEM image is illustrated in figure 3(b), it can be observed that the particle diameter is about 80 nm.…”
Section: Nano-silver Colloidmentioning
confidence: 91%
“…Amplitude analysis involves collecting particle pulses using high-speed Analog-to-Digital Converter (ADC) and analyzing the pulse amplitude to obtain multiple pieces of information, such as pulse shape and amplitude [13][14][15]. However, this method suffers from low timing accuracy and high costs for a large number of channels [16]. Time analysis, on the other hand, directly collects the time at which the pulse is detected, providing high timing accuracy, short dead time, fast processing speed, and support for numerous channels [17].…”
Section: Introductionmentioning
confidence: 99%